Saving the Last Unicorns: The Genetic Rescue of Florida’s Pillar Corals - Neely, Karen L.; Lewis, Cynthia L.; O’Neil, Keri; Woodley, Cheryl M.; Moore, Jennifer; Ransom, Zach; Moura, Amelia; Nedimyer, Ken; Vaughan, David (Frontiers in Marine Science, 2021)
As stony coral tissue loss disease (SCTLD) swept through the Florida Reef Tract, one of the most severely impacted species was the iconic pillar coral, Dendrogyra cylindrus. As the species’ population experienced a precipitous decline, a collaborative rescue project collected colony fragments for safekeeping at onshore and offshore nursery facilities. Between 2015 and 2019, a total of 574 fragments representing 128 genotypes were collected. These are currently dispersed among five facilities where they continue to provide opportunities to 1) refine best husbandry practices for D. cylindrus, 2) develop treatment options for SCTLD that have been adapted for use on other species, 3) maximize growth and fragmentation to provide the live tissue needed for eventual restoration, and 4) provide a source of parent colonies for assisted sexual reproduction and new genetic diversity. With the wild pillar coral population in Florida at the end of 2020 at less than 6% of its known 2014 population and continuing to decline, the rescued ex situ colonies represent the entirety of the restoration potential for this species in Florida.